Tipe Kepribadian Ekstrover Tokoh Utama Novel Ganjil Genap Karya Almira Bastari: Kajian Psikoanalisis Carl Gustav Jung : Indonesia - Effendi, Desy Irafadillah; Dermawan, Taufik; Sulistyorini, Dwi; Tamara, Widia (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the extroverted personality type of the main character in the novel Ganjil Genap by Almira Bastari. The method used is descriptive qualitative method with an objective approach. The data used in this study are in the form of words, sentences, or paragraphs related to narration, dialogue, and behavior that indicate the extroverted personality type of the main character in the novel Ganjil Genap. The source of the data in this study is the novel Ganjil Genap by Almira Bastari. The instrument used for data collection in this study was the researcher himself as the key instrument. The data collection technique in this study was carried out using reading and note-taking techniques with intensive, careful and repetitive reading of the novel Ganjil Genap as a process of searching for data that contains extroverted personality types, marking data according to research problems and recording data. Data analysis techniques, researchers used the Milles & Huberman model by reducing data, presenting data and drawing conclusions. The results of the research show that there is an extroverted personality type in the novel Ganjil Genap. The extroverted personality types found in the novel Ganjil Genap are extroverted-thinking, extroverted-feeling, extroverted-sensing and extroverted-intuitive. The researcher found that the extroverted personality type in the novel Ganjil Genap in the extroverted-thought-extroverted-feeling way is more dominant than the extroverted-sensed and extroverted-intuitive. The result of this research are also can increase reading interest and appreciate literaturre enthusiasts. Give benefits for education can be a reference for teaching materials and lessons from the essence of educational values contained in novels.